THE POSSIBILITY OF INTRODUCING COMPULSORY VACCINATION AGAINST COVID-19: APPLYING THE PRINCIPLE OF PROPORTIONALITY AND ANALYSIS OF THE EXISTING CASE-ALW OF THE EUROPEAN COURT OF HUMAN RIGHTS AND THE CONSTITUTIONAL COURT OF THE REPUBLIC OF CROATIA - Marochini Zrinski, Maša (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
Article 8 of the Convention for the Protection of Human Rights and Fundamental Freedoms protects individuals from the so-called involuntary medical treatments within the framework of the right to respect for private life. Given that the rights guaranteed under Article 8 are not absolute but qualified rights (that can be limited for the reasons enlisted in paragraph 2 of the same Article), it is crucial to examine the necessity and proportionality of the measures adopted by the state when deciding on the admissibility of these limitations. Through its jurisprudence, the European Court of Human Rights dealt with the issue of involuntary medical treatment, while it dealt with the issue of compulsory vaccination (of children) in only one case, Vavrička and others v the Czech Republic. Having in mind the circumstances from April 2021 (when the decision was made) and that is the peak of the fight against the pandemic caused by the COVID-19 disease, the fact that the case was decided by the Grand Chamber, as well as that at the time there were already applications against Greece and France before the Court concerning compulsory vaccination against the COVID-19 disease, it is difficult to escape the impression that the Court, answering the questions in the case of Vavrička and others, also had the aforementioned applications in mind. The importance of the Court’s decision in the case of Vavrička and others and the criteria stated in it for determining the proportionality and necessity of the measure of compulsory vaccination, as well as the width of the margin of appreciation enjoyed by states, is therefore evident. Furthermore, the paper will present the decisions of the Constitutional Court of the Republic of Croatia on the issue of compulsory vaccination of children. More will be said about the aforementioned applications before the Court where the applicants claimed how their Article 8 right was violated due to the introduction of compulsory vaccination against the COVID-19 disease for certain categories of employees, mainly for the purpose of projecting the direction in which the ECtHR will go when deciding the case. Finally, the emphasis will be on the idea that, although the status of compulsory vaccination against the COVID-19 disease before the Court has yet not been resolved, current conclusions regarding the proportionality of the measure of compulsory vaccination of children enables the formation of certain conclusions. For this reason, great attention will also be given to the doctrine of the margin of appreciation together with the concept of "weighing" the rights of individuals against the protection of certain legitimate goals, that is, the examination of necessity and proportionality by the ECtHR.
Keywords: European Convention on Human Rights; Article 8; involuntary medical treatment; compulsory vaccination proportionality; margin of appreciation; COVID-19.